Cisplatin alters the function and expression of N-type voltage-gated calcium channels in the absence of morphological damage of sensory neurons. Issue 1 (December 2017) - Leo, Markus; Schmitt, Linda-Isabell; Jastrow, Holger; Thomale, Jürgen; Kleinschnitz, Christoph; Hagenacker, Tim
Platinum-based chemotherapeutic agents, such as cisplatin, are still frequently used for treating various types of cancer. Besides its high effectiveness, cisplatin has several serious side effects. One of the most common side effects is dorsal root ganglion (DRG) neurotoxicity. However, the mechanisms underlying this neurotoxicity are still unclear and controversially discussed. Cisplatin-mediated modulation of voltage-gated calcium channels (VGCCs) in the DRG neurons has been shown to alter intracellular calcium homeostasis, a process critical for the induction of neurotoxicity. Using the whole-cell patch-clamp technique, immunostaining, behavioural experiments and electron microscopy (EM) of rat DRGs, we here demonstrate that cisplatin-induced neurotoxicity is due to functional alteration of VGCC, but not due to morphological damage. In vitro application of cisplatin (0.5 µM) increased N-type VGCC currents ( I Ca(V) ) in small DRG neurons. Repetitive in vivo administration of cisplatin (1.5 mg/kg, cumulative 12 mg/kg) increased the protein level of N-type VGCC over 26 days, with the protein level being increased for at least 14 days after the final cisplatin administration. Behavioural studies revealed that N-type VGCCs are crucial for inducing symptoms of cisplatin-related neuropathic pain, such as thermal and mechanical hyperalgesia. EM and histology showed no evidence of any structural damage, apoptosis or necrosis in DRG cells after cisplatin exposure for 26 days. Furthermore, no nuclear DNA damage in sensory neurons was observed. Here, we provide evidence for a mainly functionally driven induction of neuropathic pain by cisplatin.